PEMANFAATAN EKSTRAK ETANOL KULIT RAMBUTAN (Nephelium lappaceum. L) SEBAGAI KRIM ANTIOKSIDAN - Hamsinah Hasan; M Ilham Tomagola; Suci Mayasari (Jurnal Farmasi UIN Alauddin Makassar, 2018)
The rind of Rambutan was consumed by citizen just becomes waste.  Rambutan with Latin Nephelium lappaceum. L of the Sapindaceae tribe of the skin can be used as an antioxidant that has been stained by Thitilertdecha, et al mention that the phenolic component of the skin of rambutan fruit (Nephelium lappaceum L), among others, is geranin and corilagin is a group of flavonoids, and alegat acid from tannins class. Based on this, we will conduct research and formulate rambutan rind extract into cream preparations that have an antioxidant effect. The rambutan rind extract was obtained by using maseration method with 70% ethanolic and the viscous extract followed by testing of antioxidant activity by using DPPH method, obtained by IC50 22.774 μg / mL. The formula is varied with three emulgators. Formula I uses 2% TEA emulgator, Formula II Tween 80 and Span 80 3%, and 1% sodium lauryl sulphate. This antioxidant cream formula is physically tested for stability, including organoleptic test, emulsion type, pH measurement, viscosity measurement, forced conditions, homogeneity and flow type. Then proceed with testing the emulsion type of the cream preparation. The creamy formula of rambutan skin ethanol extract with a pharmaceutically stable 1% sodium lauryl sulfate emulgator